Student muckrakers: Applying lessons from non-profit investigative reporting in the US - Bill Birnbauer (Asia Pacific Network, 2011)
Drawing on the growth of non-profit investigative reporting centres in the United States, many of which are located in universities, this article proposes the creation of an Australia-New Zealand-Pacific network of university journalism students who collaborate to produce multi-media stories for a website. Tentatively called ‘UniMuckraker’, the project envisages that teaching with the ‘live ammunition’ of real journalism would provide an authentic, contextual and team-oriented approach to higher education learning experiences as well as producing quality journalistic content. In conceptualising the model, the article first examines contemporary trends in American investigative reporting with a focus on the increasing number and influence of non-profit centres that have been created following mass layoffs of journalists and closures in the established press. It finds a new willingness by mainstream media to collaborate with highly-specialised non-profit ‘factories’ that produce investigative stories but notes that the editor/publisher distinction is blurred further in the non-commercial model and that questions have been raised about the motives of the philanthropic funders of non-commercial investigative reporting.